2017
DOI: 10.1177/0022034517718790
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155-3p Mediates TNF-α-Inhibited Cementoblast Differentiation

Abstract: Periodontitis is a prevalent and chronic inflammatory disease that is interrelated with systemic health. Periodontitis can be promoted by tumor necrosis factor α (TNF-α). Cementum, a vital part of the periodontium, is a bone-like mineralized tissue that is produced by cementoblasts. Our laboratory previously revealed that TNF-α inhibits cementoblast differentiation and mineralization. However, how TNF-α modulates cementoblast differentiation and mineralization remains largely unknown. MicroRNA-155 (miR-155) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 40 publications
6
39
3
Order By: Relevance
“…5C, 5D). These findings are consistent with previous reports that TNF-α is a proinflammatory factor that inhibits cellular cementoblastic differentiation [28,63]. However, other cyto-/chemokines, such as IL-6, Eotaxin, GM-CSF and IFN-γ, were not found to exert significant influences on the expression of CEMP-1 (Supporting Information Fig.…”
Section: Stem Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…5C, 5D). These findings are consistent with previous reports that TNF-α is a proinflammatory factor that inhibits cellular cementoblastic differentiation [28,63]. However, other cyto-/chemokines, such as IL-6, Eotaxin, GM-CSF and IFN-γ, were not found to exert significant influences on the expression of CEMP-1 (Supporting Information Fig.…”
Section: Stem Cellssupporting
confidence: 92%
“…6A, 6B), suggesting that the contribution of the JNK pathway to M2 Mφ-enhanced cementoblastic differentiation may be mediated by other signals, such as exosomes [67,68]. There is evidence that the AKT signaling pathway plays a key role in the production of VEGF and IL-10 [69][70][71], and other cytokines, such as IFN-γ and TNF-α, can also regulate this process by activating the AKT or JNK signaling pathway [62][63][64][65][66][67][68][69][70][71][72][73], suggesting that the cytokine-cytokine and cytokine-pathway interactions are bidirectional and very complex. Although further research is necessary before the signals involved in M2-enhanced cementoblastic differentiation can be clarified, the data obtained in the present study suggest that modulation of Mφs in an in vivo milieu to positively influence PDLSCs can be useful for true periodontal regeneration.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Unlike IL-1β, other inflammatory factors such as TNF-α do not cause similar osteogenic promoting effects (36)(37)(38)(39). Previous findings have shown that TNF-α significantly inhibits osteogenic differentiation potential of MSCs at different concentrations (36)(37)(38)(39). In the present study, when IL-1β concentration was increased to 10 ng/ml, osteogenic promotion disappeared and osteogenic genes were downregulated.…”
Section: Discussioncontrasting
confidence: 47%
“…The present results suggested that the addition of IL-1β at 0.01-1 ng/ml under osteogenic induction significantly enhanced the osteogenic differentiation of MBMMSCs, and this was demonstrated by the mRNA expression levels of downstream osteogenic genes. Unlike IL-1β, other inflammatory factors such as TNF-α do not cause similar osteogenic promoting effects (36)(37)(38)(39). Previous findings have shown that TNF-α significantly inhibits osteogenic differentiation potential of MSCs at different concentrations (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 96%
“…In the previous study of our lab, tumor necrosis factor‐α (TNF‐α) has an effect on cementoblast differentiation and apoptosis (Y. L. Wang et al, ). Then, the mechanisms underlying the effect of TNF‐α on cementoblast showed that microRNA‐155‐3p regulates TNF‐α‐inhibited cementoblast differentiation (X. Wang et al, ). However, the relevance of miRNA to the inflammatory response in cementoblasts remains unknown.…”
Section: Introductionmentioning
confidence: 99%